2016
DOI: 10.1186/s12966-016-0406-6
|View full text |Cite
|
Sign up to set email alerts
|

Associations between liking for fat, sweet or salt and obesity risk in French adults: a prospective cohort study

Abstract: BackgroundIndividual sensory liking appears to be an important determinant of dietary intake and may consequently influence weight status. Cross-sectional studies have shown positive association between fat liking and weight status and equivocal results regarding salt and sweet liking. Moreover, the contribution of dietary intake to explain this relationship has not been studied yet. We investigated the prospective association between sensory liking for fat, sweet or salt and the onset of obesity over 5 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 50 publications
5
58
0
2
Order By: Relevance
“…In a world abundant in foods rich in sugar or its derivatives, sweetened beverages, and processed foods for young children [43], growing children's heightened preferences for sweets can make them susceptible to excessive sugar consumption [44]. The role of early nutritional experience and its impact on the risk of overweight and obesity of children is well documented [45,46]. Breastfeeding, early exposure to a wide range of products varied in taste, determine later preferences and dietary habits [17,47].…”
Section: Discussionmentioning
confidence: 99%
“…In a world abundant in foods rich in sugar or its derivatives, sweetened beverages, and processed foods for young children [43], growing children's heightened preferences for sweets can make them susceptible to excessive sugar consumption [44]. The role of early nutritional experience and its impact on the risk of overweight and obesity of children is well documented [45,46]. Breastfeeding, early exposure to a wide range of products varied in taste, determine later preferences and dietary habits [17,47].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, adolescents with early onset and severe obesity displayed lower recognition thresholds, indicating higher acuity, and higher sensitivity for both sucrose and salt compared to the non-obese adolescents [25]. Finally, some studies found no association between body composition and salt taste sensitivity threshold [26], and no association between obesity and salt liking [27]. On the contrary, fat-liking was found to be associated with an increased risk of obesity [27].…”
Section: Introductionmentioning
confidence: 95%
“…Finally, some studies found no association between body composition and salt taste sensitivity threshold [26], and no association between obesity and salt liking [27]. On the contrary, fat-liking was found to be associated with an increased risk of obesity [27]. Moreover, animal models have shown that high-fat diet resulted in obesity and pronounced loss of taste buds, indicating that taste loss could be a metabolic consequence of the obese state [28].…”
Section: Introductionmentioning
confidence: 99%
“…Reducing fat consumption has become a key challenge for modern societies since the high consumption of fatty products has been associated with obesity and its associated pathologies, such as cardiovascular diseases, cancer, diabetes 1, 2 . However, the attraction of the consumer to fatty products is not well understood, and a strong variability in liking fat is observed in the population.…”
Section: Introductionmentioning
confidence: 99%